2014
DOI: 10.1590/0001-3765201420130404
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative potential of Vernonia cinerea on chronic constriction injury of sciatic nerve induced neuropathic pain in rats

Abstract: The aim of the present study is to investigate the ameliorative potential of ethanolic extract of whole plant of Vernonia cinerea in the chronic constriction injury (CCI) of sciatic nerve induced neuropathic pain in rats. Behavioral parameters such as a hot plate, acetone drop, paw pressure, Von Frey hair and tail immersion tests were performed to assess the degree of thermal, chemical and mechanical hyperalgesia and allodynia. Biochemical changes in sciatic nerve tissue were ruled out by estimating thiobarbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Our recent findings revealed that alteration of a neuronal microvascular system is primary cardinal signs for the damage and degeneration of the nervous system [[68], [69], [70]]. Furthermore, some of our studies and other laboratory reports recommended that plant extracts and nutritional products of Acorus calamus [51,70], Butea monosperma [71], Swietenia mahagoni [72], Ocimum sanctum [73] and Vernonia cinerea [74] mitigate neuropathic pain symptoms. Phytoconstituents like puerarin [75], bulleyaconitine A [76], thymoquinone, epigallocatechin gallate, lycopene and resveratrol [17] produced an anti-neuralgic effect.…”
Section: Discussionmentioning
confidence: 88%
“…Our recent findings revealed that alteration of a neuronal microvascular system is primary cardinal signs for the damage and degeneration of the nervous system [[68], [69], [70]]. Furthermore, some of our studies and other laboratory reports recommended that plant extracts and nutritional products of Acorus calamus [51,70], Butea monosperma [71], Swietenia mahagoni [72], Ocimum sanctum [73] and Vernonia cinerea [74] mitigate neuropathic pain symptoms. Phytoconstituents like puerarin [75], bulleyaconitine A [76], thymoquinone, epigallocatechin gallate, lycopene and resveratrol [17] produced an anti-neuralgic effect.…”
Section: Discussionmentioning
confidence: 88%
“…There are also several non-peptide small molecules under preclinical and clinical trials but till no successful outcome has been noticed. But of course, because of the small size and non-peptide nature they can lead to the development of molecule that can follow an alternate route with fewer side effects and more specific to the receptor [215][216][217][218][219][220][221]. In recent years, lots of review and research have been published on recent advancements of nanotechnology and their application on neurological disease as well as NP [222][223][224][225][226][227][228][229][230][231][232][233].…”
Section: Mechanism For Excitatory Effect Of Drugsmentioning
confidence: 99%
“…The antiinflammatory effect of hydroalcoholic extract of Lampaya medicinalis has been attributed to presence of flavonoids in the extract [18]. The ameliorative potential of ethanolic extract of whole plant of Vernonia cinerea in the Chronic Constriction Injury (CCI) of sciatic nerve induced neuropathic pain in rats has also been attributed to flavonoids [19]. The antinociceptive and anti-inflammatory of flower extract of Alangium salvifolium has been attributed to presence of alkaloids and flavonoids in the extract [20].…”
Section: Therapeutic Potentialmentioning
confidence: 99%